Lessons in Student Motivation - Errol Craig Sull (Park University, 2007)
The tools students have at their ready to do well are really amazing: engaging, thorough, and colorful textbooks; the Internet, of course; faculty who know how to teach and offer a plethora of information; and seemingly endless possibilities for optimal learning environments. Yet with all these improved "mousetraps" there is one factor that, if missing, will keep each of these silent - and the student will learn little or naught: motivation. Indeed, if the student is not motivated to learn, and his or her motivation is not kept up throughout a course, there is little the student will take away from the course.